The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.1002/jbm.b.35395
|View full text |Cite
|
Sign up to set email alerts
|

Zinc‐doped hydroxyapatite as a pH responsive drug delivery system for anticancer drug 6‐mercaptopurine

Marcel Jakubowski,
Łukasz Majchrzycki,
Aleksej Zarkov
et al.

Abstract: Abstract6‐Mercaptopurine (6MP) is commonly used in the treatment of acute lymphoblastic leukemia as an important agent in maintenance therapy. Despite its therapeutic benefits, 6MP has some limitations during therapy. Taking into account the disadvantages during 6MP therapy, there is a great need to create an appropriate delivery system for this drug. 6MP contains in its structure nitrogen and sulfur atoms capable of forming coordination compounds with metal ions, for example zinc. Therefore, in this work, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
0
0
Order By: Relevance
“…Thus, these modifications also have a considerable impact on the biological response of doped HAp, both in vitro and in vivo . 5 To date, different research groups have reported the synthesis of doped-HAp materials and utilized such materials in a variety of fields including medicine, 6 catalysis, 7 photocatalysis, 8 bone tissue engineering, 9 drug delivery 10 and so on. Out of these, photocatalysis is one of the most widely explored applications of modified hydroxyapatite materials.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, these modifications also have a considerable impact on the biological response of doped HAp, both in vitro and in vivo . 5 To date, different research groups have reported the synthesis of doped-HAp materials and utilized such materials in a variety of fields including medicine, 6 catalysis, 7 photocatalysis, 8 bone tissue engineering, 9 drug delivery 10 and so on. Out of these, photocatalysis is one of the most widely explored applications of modified hydroxyapatite materials.…”
Section: Introductionmentioning
confidence: 99%